FAKTOR-FAKTOR YANG MEMPENGARUHI KOLEKTIBILITAS KREDIT PETANI DI BANK BRI CABANG TOMOHON TIMUR - Willem N. Siwi; Tommy F. Lolowang; Eyverson Ruauw; Ellen G. Tangkere (COCOS, 2015)
ABSTRACT Willem Nicolas Siwi. Factors that affect the collectability of farmers in East Tomohon BRI bank branch. Under the guidance of Dr. Ir Tommy Lolowang, MSi (Chairman), Ir. Eyverson Ruauw, MS (Member), and Ellen. G. Tangkere SP, MSi (Member). The purpose of this study is to determine what are the factors that affect the ability of borrowers to repay loans of farmers, particularly in the BRI bank branch tomohon. This study uses a sample is not likely. The data used is primary data obtained through interviews with Bank Employees Field collector, especially on the characteristics of farmer customers who struggle to pay loans, and secondary data is primary data that has been processed. The variables measured were age, sex, marital status, education, long occupied dwelling, possession of a residence, a distance of BRI with the location of the home and the number of family dependents, other loans, business experience, business turnover, collateral, interest rate, and term credit payback time. The data has been obtained from BRI bank over the last year, were analyzed to determine the characteristics of the debtor where the most significant effect on the collectibility of the loans of farmers. Results of the study determined that the BRI branch captive eastern Tomohon experiencing nonperforming loans are largely at the age of 31-40 years, with female sex, having the status of married, graduated from high school education, long occupied a place to stay for 1-10 years, ownership of residence is a self-owned, has a location within the house with BRI as far as 1-10 km and has a number of family dependents of 2-3 people, have other loans, between 0-10 years of business experience, has a business turnover of between 1,000,000.00 - Rp20 .000.000,00 per month, has a household collateral, high interest rates and are in a payback period of between 7-12 months credit. And the factors that influence the real (significant) towards repayment of credit is long occupied dwelling, other loans and interest rates. Advice can be given by the researchers in this study that, when considering the value of the variable long odds ratio occupied dwelling, other loans, and interest rates on the loans at BRI branches east Tomohon can be focused on prospective borrowers with long residence occupies more than 1 years, has no other loans and debtors of understanding regarding his willingness to pay the installments with interest charges apply. BRI should Tomohon eastern branch is expected to be more selective in deciding which prospective borrowers may receive loans by considering various things in particular turnover of the businesses owned by prospective borrowers and frequency / intensity in obtaining loans. Business condition of borrowers in the future have to be predicted because there is a possibility of success or failure of the business in the future and it affects the value of the business turnover is becoming one of the benchmark loan repayment capacity. Keywords: Credit, BRI, Collectability